Effects of varying pandemic restrictions on the health‐related behaviours of Australian children. (7th October 2022) - Robinson, Lauren; Measey, Mary‐Anne; Efron, Daryl; Mundy, Lisa; Hoq, Monsurul; Rhodes, Anthea
Abstract : Aim: To explore the effects of COVID‐19 pandemic restrictions varying in severity and duration on health‐related behaviours in children aged 5–17 years. Methods: We used data from the Royal Children's Hospital National Child Health Poll, an online cross‐sectional survey of Australian caregivers. The survey assessed 1222 caregivers' perceived changes in health‐related behaviours (physical activity, sleep, screen‐time, diet, outdoor activity, family and peer connectedness) of 2011 children aged 5–17 years in a typical week from June to September 2020 (when jurisdictions experienced varying restriction severity and duration) compared to retrospective reports of behaviour before March 2020 (pre‐pandemic). To compare the effects of varying restriction severity in Victoria, New South Wales (NSW) and other states and territories on health‐related behaviours binary logistic regression was used, adjusting for caregiver demographics and weighted to reflect Australia's parent population. Results: Compared to pre‐pandemic, Victoria's restrictions had a greater impact on child health‐related behaviours compared to NSW restrictions and an even stronger impact compared to other states and territories which experienced few or no restrictions. A greater proportion of Victorian children reported more recreational screen time (71.3%) than NSW (53.9%) and other states and territories (34.5%) and less physical activity (57.2%) than NSW (30.3%) and other states and territories (26.5%). Victorian children reported less outdoor activity (62.6%) than NSW (32.0%) and other states and territories (25.2%), and less social connectedness (68.0%) than NSW (35.4%) and other states and territories (27.3%). Conclusions: More severe and longer COVID‐19 pandemic restrictions are associated with greater impacts and predominantly more negative impacts to children's health‐related behaviours. These should be mitigated through policies and programs to encourage healthier life‐styles.